Network-enhanced photoresponse time of Ge nanowire photodetectors - Yan, Chaoyi (2012)
We demonstrated that the photoresponse time of Ge nanowire (NW) photodetectors could be greatly improved by using percolated NW networks (instead of single NW) as the active detection channels. Although the reset time for single-NW devices was >70 s, a fast reset time <1 s was observed for NW-network devices. The enhancement was attributed to the barrier-dominated conductance for network devices, which was not available in single-NW devices. The network structures provide ideal alternative solutions to the conventional single-NW photodetectors, given their superior performances and low-cost fabrication processes.